Answer:
[tex]x=\frac{3}{2}\\ y=\frac{1}{2}[/tex]
Step-by-step explanation:
[tex]y=-x+2\\y=3x-4[/tex]
Let's solve one of them for x.
[tex]y=3x-4[/tex]
Add 4
[tex]y+4=3x[/tex]
Divide by 3.
[tex]x=\frac{y+4}{3}[/tex]
Now, plug the value of y in the formula, or you can plug the value of x in the other equation. I'll take this one.
[tex]x=\frac{y+4}{3}[/tex]
[tex]x=\frac{(-x+2)+4}{3}[/tex]
[tex]x=\frac{-x+2+4}{3}[/tex]
[tex]x=\frac{-x+6}{3}[/tex]
Multiply by 3 to get rid of the denominator.
[tex]3x=-x+6[/tex]
add x
[tex]3x+x=6[/tex]
Combine like terms;
[tex]4x=6[/tex]
Divide by 4.
[tex]x=\frac{6}{4}[/tex]
Simplify.
[tex]x=\frac{3}{2}[/tex]
Now that you found the value of x, replace it in any of the equations to find y.
[tex]y=-x+2\\y=-(\frac{3}{2})+2\\ y=-\frac{3}{2}+2[/tex]
[tex]y=\frac{-3+2*2}{2} \\y=\frac{-3+4}{2} \\y=\frac{1}{2}[/tex]
Proof:
[tex]y=3x-4\\\frac{1}{2}=3(\frac{3}{2})-4\\\frac{1}{2}=(\frac{9}{2})-4[/tex]
[tex]\frac{1}{2}=\frac{9-4*2}{2}[/tex]
[tex]\frac{1}{2}=\frac{9-8}{2}[/tex]
[tex]\frac{1}{2}=\frac{1}{2}[/tex]